Urban vegetation change after a hundred years in a tropical city (San José de Costa Rica) - Julián Monge-Nájera; Gabriela Pérez-Gómez (Revista de Biología Tropical, 2010)
Urban vegetation is of key importance because a large proportion of the human population lives in cities. Nevertheless, urban vegetation is understudied outside central Europe and particularly, little is known about the flora of tropical Asian, African and Latin American cities. We present an estimate of how the vegetation has changed in the city of San José, Costa Rica, after about one century, with the repeat photography technique (based on a collection of 19th and early 20th century photographs by José Fidel Tristán and others) and with data from the Costa Rican National Herbarium. We found little vegetation change in the landscape of San José during the 20th century, where a total of 95 families and 458 species were collected in the late 19th and early 20th century. The families with most species were Asteraceae, Fabaceae, Poaceae, Lamiaceae, Euphorbiaceae, Solanaceae, Cyperaceae, Acanthaceae, Malvaceae, Piperaceae and Verbenaceae. Similar results have been found in Europe, where the number of plant species often is stable for long periods even when the individual species vary. Rev. Biol. Trop. 58 (4): 1367-1386. Epub 2010 December 01. La vegetación urbana es de vital importancia ya que una proporción importante de la población humana vive en ciudades. Sin embargo, esta vegetación es poco estudiada fuera del centro de Europa y se sabe particularmente poco sobre la flora urbana de las ciudades tropicales de Asia, África y América Latina. Aquí presentamos una estimación de cómo ha cambiado la vegetación en la ciudad de San José, Costa Rica, durante un siglo, con la técnica de la fotografía repetida (sobre la base de una colección de fotografías del siglo XIX y principios del siglo XX hechas por José Fidel Tristán y otros) y con los datos del Herbario Nacional de Costa Rica. Encontramos pocos cambios en el paisaje de San José durante el siglo XX. En la ciudad se recolectaron 95 familias y 458 especies entre finales del siglo XIX y principios del XX. Las familias con más especies fueron Asteraceae, Fabaceae, Poaceae, Lamiaceae, Euphorbiaceae, Solanaceae, Cyperaceae, Acanthaceae, Malvaceae, Piperaceae y Verbenaceae. Los resultados son similares a los de Europa, donde el número de especies de plantas a menudo es estable durante largos períodos, aunque las especies individuales varíen.